2020
DOI: 10.1186/s13018-020-01758-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of intravenous and topical tranexamic acid efficiently reduces blood loss in patients aged over 60 operated with a 2-level lumbar fusion

Abstract: Purpose: The current study was conducted to assess the efficacy and safety of the intravenous (IV) administration combined with topical administration of tranexamic acid (TXA)in patients (aged over 60) scheduled for a 2-level lumbar fusion surgery. Methods: Two hundred eighty patients scheduled for a 2-level lumbar fusion surgery were randomized into four groups, including an IV group, a local group, a combined group, and a control group. Patients in the combined group, in the IV group, in the topical group, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
1
23
0
Order By: Relevance
“…Based on the outcomes of pool of 5 studies, the most important finding of this meta-analysis was that the administration of TXA could significantly reduce total blood loss (MD = − 239.60, 95% CI − 332.74 to − 146.46, P < 0.00001) and wound complications (RR = 0.34, 95% CI 0.12 to 0.97, P = 0.04). This is consistent with the evidence that TXA can also reduce total blood loss in arthroplasty, spine, and other orthopedic surgeries [ 13 , 23 , 24 ]. Indeed, blood loss is inevitable when the medullary cavity is exposed during the tibial osteotomy.…”
Section: Discussionsupporting
confidence: 90%
“…Based on the outcomes of pool of 5 studies, the most important finding of this meta-analysis was that the administration of TXA could significantly reduce total blood loss (MD = − 239.60, 95% CI − 332.74 to − 146.46, P < 0.00001) and wound complications (RR = 0.34, 95% CI 0.12 to 0.97, P = 0.04). This is consistent with the evidence that TXA can also reduce total blood loss in arthroplasty, spine, and other orthopedic surgeries [ 13 , 23 , 24 ]. Indeed, blood loss is inevitable when the medullary cavity is exposed during the tibial osteotomy.…”
Section: Discussionsupporting
confidence: 90%
“…It, as a synthetic antifibrinolytic drug, can reduce surgical bleeding by inhibiting fibrinolysis and stabilizing blood clots (8). Studies have reported that intravenous (iv)TXA can effectively reduce perioperative blood loss in PLIF (9)(10)(11)(12). Red blood cell (RBC), hemoglobin (HB) and hematocrit (HCT) are commonly used clinical indicators to monitor the course of anemia.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, spine surgeon should consider the effect of PLIF, and on the other hand, consider how to reduce perioperative blood loss 13 . Many scholars have www.nature.com/scientificreports/ studied that intravenous TXA can safely and effectively reduce perioperative blood loss in PILF patients [5][6][7][8] . There are various options for using TXA during the perioperative period of spinal surgery, such as oral medication, local medication, intravenous medication, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Tranexamic acid (TXA) is a synthetic derivative of lysine, a synthetic anti fibrinolytic drug that could reduce surgical bleeding by inhibiting fibrinolysis and stabilizing blood clots 4 . Many studies have shown that intravenous TXA can effectively reduce perioperative blood loss in PLIF 5 8 . Meanwhile, in our previous studies, we confirmed that preoperative intravenous unit dose TXA in PLIF can safely and effectively reduce intraoperative and postoperative blood loss without affecting postoperative coagulation function indicators 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%